PENERAPAN METODE BLENDED LEARNING BERBASIS TIK UNTUK MENINGKATKAN PEMAHAMAN KONSEP PADA MATAKULIAH LISTRIK MAGNET II - Ayu Fitri Amalia (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2017)
Blended learning is the integration traditional classroom, e-learning, and selflearning methods using ICT based learning. One of them is through Edmodo supported by sufficient internet facilities. The aim of the research was to know the design of learning methods and the utilization of ICT based of blended learning in order to improve the understanding of the concepts in the 2nd Electromagnetic course. The reaserch was a descriptive class action by using qualitative and quantitative approach. All students of Physics Education in FKIP UST who take the 2nd Electromagnetic course were the subject of research. The sample was 28 students as respondents. The sample taking technique in the research used total sampling technique. The results showed that the utilization of Edmodo as the elearning tools in blended learning method was still at a moderate level. It was beacuse for students who took 2nd Electromagnetic course in 2015/2016 academic year were the first experience were not accustomed to active. Furthermore, it was beacuse of the limited internet connection facility. ICT-based of blended learning method as an appropriate educational technology effectively enough to help the learning process so that the lecturers and students could communicate interactively without place restrictions in anytime and anywhere.Keywords : Blended learning, Edmodo